THE ARCHEOLOGY OF 'HUMANISM' - Birus, Hendrik (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1994)
This essay plots the historical course of the concept of "humanism" as it developed in the Western tradition. Combining analysis with concrete historical research, it compares and contrasts the concept's meanings, discussing the term in modernity and in the Renaissance, down to its early appearances in Cicero's texts. In addition to citing relevant secondary literature, it refers to texts by Heidegger, Marx, Hegel, and Erasmus, among others.